Endoscopic lysis of bladder scar associated with Hunner's lesions: A new technique - Sonia Bahlani; Robert Moldwin (Asian Journal of Urology)
Objective: Five to ten percent of interstitial cystitis/bladder pain syndrome (IC/BPS) patients have Hunner's lesions (HL), areas of non-specific inflammation and scarring. The poor quality of life of patients with HL is entwined in associated pain and loss of bladder capacity. Although the decrease in bladder capacity is usually dependent on pain, it may also be dependent upon scarring and associated compliance changes produced by the inflammatory process. This report reviews the potential role of endoscopic scar lysis using the holmium laser in the management of these patients whose only other therapeutic option is urinary diversion. Methods: Two patients with HL and “end stage” bladders who underwent holmium laser division of bladder wall scar/tethering were identified. Clinical data were reviewed with emphasis on safety and efficacy. Results: Both patients selected for this procedure underwent holmium laser lysis of known scar tissue in an effort to increase bladder capacity and improve symptoms of urinary frequency and pain with bladder filling. The median age of patients who underwent the procedure was 63 (59–67) years. Incisions were made with the holmium laser at frequencies of 3–10 Hz of 300–700 J along the region of scarring. All procedures were performed by the same practitioner. There was an increase in bladder capacity by 58.3% (50.0%–66.7%). During a mean follow-up of 4.2 years, there appeared to be a significant improvement with an increase in interval time between voids and a decrease in pain with bladder filling. Conclusion: Patients with IC/BPS may be severely debilitated by a clinically significant decrease in their bladder capacity, especially in the face of HL. The use of the holmium laser to incise regions of scar and bladder wall tethering may produce a clinically significant and durable increase in bladder capacity. The use of this technique as a means of treating bladder scarring poses an excellent adjunct to existing treatment strategies.